PSYCHOLOGICAL DISTRESS AND ACADEMIC SELF-EFFICACY OF COLLEGE STUDENTS: THE MODERATING ROLE OF ANXIETY AMIDST THE COVID-19 PANDEMIC - Muñoz, Kaila Mei; Lozano, Ma. Arnella; Guintu, Princess Diane; Garcia, Irvin Jither; Embalsado, Justin Vianey (International Journal of Education, 2023)
The distress and anxiety brought about by the academic demands negatively influences student performance during the abrupt shift to full-online classes. However, the literature indicates that self-efficacy significantly alleviates the negative effect of distress and anxiety.The current study aims  to determine the relationship of COVID-19 related distress and academic self-efficacy as well as investigate if anxiety is a moderator that aggravates the distress of Angeles University Foundation college students. A total of 223 college students’ participants were acquired from a voluntary convenience sample and participants answered the questionnaires through Google Forms, namely: The Online Learning Self-Efficacy (OLSE), The Kessler Psychological Distress Scale (K6), and The Coronavirus Pandemic Anxiety Scale (CPAS-11). Additionally, all statistical analyses were conducted using SPSS 23. Moreover, the hierarchical regression was conducted to determine if COVID-19 distress predicted academic self-efficacy (ASE) with anxiety as the moderator. The findings indicate that COVID-19 distress and anxiety negatively affect the beliefs of the students in their capacity to perform academic tasks.   However, evidence failed to support the moderating role of anxiety between Covid-19 distress and academic self-efficacy.